Hubungan Pola Asuh Orang Tua Dengan Perilaku Jajan Pada Anak Usia Sekolah: Literature Review - Yonathan Kristian Yuan Putra; Idris Handriana (Universitas Katolik Widya Karya Malang, 2023)
Background: School-age children are referred to as latent periods, the more independent school-age children are, the more they have problems in the selection of snacks. The findings of the Food and Drug Administration (BPOM) found several results of food content which showed 91.26% qualified, 8.71% ineligible,285 samples contained Rhodamin B, 211 samples contained Formalin, 162 samples contained Borax and 5 food samples contained Methanyl Yellow. Parenting is a factor that influences the behavior of snack, parents are the first source of information to understand about the behavior of healthy snacks in children.Objective: The purpose of this study was to foster journals regarding the relationship between snacking patterns in school-age children.Methods: Literature review method, which includes searching for journals from Elsevier, Pudmed, Google Scholer, and Garuda which received 6 journals because they have been tested based on the Critical Appraisal Checklist (JBI) instrument for analysis of Cross Sectional Studies. Then use PRISMA to select them and use the Plagiarsm Checker X application with 17% results.Results: Literature review data conducted on 6 journals that have been obtained shows that there is a relationship between parenting patterns and snack selection behavior in school age children and 1 journal there is no relationship. 6 research journals obtained the dominant value of journal 1 Lonto et al., (2019), with respondents of democratic fostering pattern category as many as 30 people or (46.9%) and 44 respondents (68.8%) with healthy snack behaviors. The better the parenting pattern applied to the child, the lower the level of snack selection behavior in the child.Suggestion: Literature review results are expected to be an educational material, especially school-age children and parents about the importance of foster care patterns to prevent snack selection behavior in school-age children.